2005
DOI: 10.1007/s10439-005-4389-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving Hollow Fiber Dialyzer Efficiency with a Recirculating Dialysate System I: Theory and Applicability

Abstract: The mathematical theory that underlies a novel non-regenerated recirculating dialysate system (RDS) for improving diffusive clearance in hemodialyzers is presented. The theory states the conditions that hemodialyzers must meet to be suitable in RDS optimization. We have verified the applicability of the RDS for several Cuprophan and polysulfone (PS) commercial dialyzers, showing that PS (synthetic) membranes achieve the highest increments of diffusive clearance. A numerical simulation analysis over more genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…The functionsR t (Q d ) for these dialyzers were calculated by linear regression in Prado et al 28 from the experimental measurements of Allen et al 2 and Leypoldt and Cheung. 19 These are presented here for convenience.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The functionsR t (Q d ) for these dialyzers were calculated by linear regression in Prado et al 28 from the experimental measurements of Allen et al 2 and Leypoldt and Cheung. 19 These are presented here for convenience.…”
Section: Methodsmentioning
confidence: 99%
“…The value of V t is taken approximately equal to the dialyzer dialysate volume with the aim of keeping the time-constant of the tank solute concentration, c t , lesser than the residence time of the dialysate through the dialyzer. 28 This condition guarantees the steady-state condition of the system, which strongly simplifies the analysis.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, Henderson [31] and Leber et al [32] showed that ultrafiltration operation not only improves the mass transfer efficiency in a hemodialysis process but can also reduce the treatment time and is tolerable by patients. Prado et al [33] designed a non-regenerating, recirculating dialysate system to improve the efficiency of a hollow fiber dialyzer.…”
Section: Introductionmentioning
confidence: 99%